Chapter 4 Box Problems
Box A
Problem a
1 | x <- c(11,15,13,8,10,16) |
Problem b
Variable | Definition |
---|---|
s.j.x.ij | $\Sigma {jx}_{ij}$ |
n.i | $n_i$ |
x.bar.i | $\bar{x}_i$ |
n.i.2 | $n_i^2$ |
WSS | $\Sigma_j(x_{ij}-\bar{x}_{i.})^2$ |
WSS | $\Sigma_j(x_{ij}-\bar{x}_{i.j})^{2}$ |
$\Sigma_j(x_{ij})$ | |
grand.mean | $\bar{x}_{..}$ |
delta.2 | $ (\bar{x}_i - \bar{x}_{..} )^{2}$ |
BSS | $n_i(\bar{x}_i - \bar{x}_{..})^2$ |
TSS | $\Sigma_j(\bar{x}_{ij}-\bar{x}_{..})^2$ |
1 | #I will call the 3 groups a, b, c |
1 | results.2 <- split(results, sample) |
Box B
Problem a
Allele change | effect | proportion | frequency change |
---|---|---|---|
AA –> AA’ | u+d-(u+a) | p | pu + pd - pu - pa |
AA’ –> A’A’ | u-a-(u+d) | q | qu-qa-qu-qd |
sum | -a(p+q)+d(p-q) | ||
=-a+d(p-q) | |||
$$= - \alpha$$ |
Problem b
Problem c
1 | h2 <- c( rep(0.09, 6), rep(0.16, 6)) |
Box C
Problem a
Derive: $$\displaystyle \frac{(\mu_s - \mu)}{\sigma^2} = \frac{Z}{B}$$ Given:
$$\displaystyle Z = \frac{1}{\sqrt{2\pi} \sigma} e^{\frac{-(T - \mu)^2}{2\sigma^2}}$$
$$\displaystyle B = \frac{1}{\sqrt{2\pi}\sigma} \int^{\infty}_{T} e^{\frac{-(x-\mu)^2}{2\sigma^2}} dx$$
$$\displaystyle \mu_s = \frac{1}{B\sqrt{2\pi}\sigma} \int^{\infty}_T xe^{\frac{-(x-\mu)^2}{2\sigma^2}} dx$$
Given the integration formulas:
$$\displaystyle \int xe^{\frac{-(x-\mu)^2}{2\sigma^2}} dx = -\sigma^2 e^{\frac{-(x-\mu)^2}{2\sigma^2}} + \mu \int e^{\frac{-(x-\mu)^2}{2\sigma^2}} dx$$
$$\displaystyle \int e^x dx = x$$
Define X as: $$X = \frac{-(x-\mu)^2}{2\sigma^2}$$ so that $$\mu_s$$ can be defined as:
$$\displaystyle \mu_s = \frac{1}{B}(\frac{1}{\sqrt{2\pi}\sigma})\int^{\infty}_T xe^Xdx$$
Evaluate the integral to obtain:
$$\displaystyle \mu_s = \frac{1}{B}[(\frac{1}{\sqrt{2\pi}\sigma})[\sigma^2e^X]|^{\infty}_T + \mu \int^{\infty}_T e^Xdx]$$
$$\displaystyle \mu_s = \frac{1}{B}[(\frac{1}{\sqrt{2\pi}\sigma})[0 - -\sigma^2e^X] + \frac{\mu}{\sqrt{2\pi}\sigma} \int^{\infty}_T e^Xdx]$$
$$\displaystyle \mu_s = \frac{1}{B}[(\frac{1}{\sqrt{2\pi}\sigma})[\sigma^2e^{\frac{-(T-\mu)^2}{2\sigma^2}}] + \frac{\mu}{\sqrt{2\pi}\sigma} \int^{\infty}_T e^{\frac{-(x-\mu)^2}{2\sigma^2}}dx]$$
Rearrange:
$$\displaystyle \mu_s = \frac{\sigma^2}{B} (\frac{1}{\sqrt{2\pi}\sigma})[e^{\frac{-(T-\mu)^2}{2\sigma^2}}] + \frac{\mu}{B} \frac{1}{\sqrt{2\pi}\sigma} \int^{\infty}_T e^{\frac{-(x-\mu)^2}{2\sigma^2}}dx$$
Substitute in B and Z:
$$\displaystyle \displaystyle \mu_s = \frac{\sigma^2Z}{B} + \mu$$
Problem b
B | i | |
---|---|---|
0.1 | 1.76 | |
0.01 | 2.66 | |
10 | 1.5 | fold change |
Problem c
1 | species <- c("cattle","swine","chicken") |
Box D
Problem a
$$\displaystyle \frac{2a}{\sigma} \equiv$$ proportionate effect
For the Drosophila example:
$$\displaystyle U - D = 12\sigma$$
$$\displaystyle \sigma^2_a = 0.3\sigma^2$$
$$\displaystyle n = \frac{(U-D)^2}{8\sigma^2_a} = \frac{(12\sigma)^2}{8(0.3)\sigma^2} = \frac{144\sigma^2}{2.4\sigma^2} = 60$$
$$\displaystyle \frac{2a}{\sigma} = 2(\frac{\sigma_a}{\sigma})\sqrt{\frac{2}{n}} = 2(\frac{\sqrt{0.3\sigma^2}}{\sigma})\sqrt{\frac{2}{60}} = 2(\frac{0.548\sigma}{\sigma})0.18 = 0.197$$
For the mouse weight example:
$$\displaystyle U - D = 8\sigma$$
$$\displaystyle \sigma^2_a = 0.25\sigma^2$$
$$\displaystyle n = \frac{(U-D)^2}{8\sigma^2_a} = \frac{(8\sigma)^2}{8(0.25)\sigma^2} = \frac{64\sigma^2}{2\sigma^2} = 32$$
$$\displaystyle \frac{\sigma_a}{\sigma} = 2\frac{\sigma_a}{\sigma}\sqrt{\frac{2}{n}} = 2\frac{\sqrt{0.25\sigma^2}}{\sigma}\sqrt{\frac{2}{32}} = 2(\frac{0.5\sigma^2}{\sigma})0.25=0.25$$
Problem b
Given that $$\displaystyle n=50, \sigma^2=66.9, \sigma^2_a=47.6$$
$$\displaystyle U-D = \sqrt{8n\sigma^2_a} = 138$$
$$\displaystyle \frac{U-D}{\sigma} = \frac{138}{\sqrt{66.9}} = 16.8$$
Box E
Problem a
Using the equations:
$\displaystyle \bar{w} = 1-p^2s-q^2t$ where q = 1-p $$\displaystyle p' = \frac{p(pw_{11} + qw_{12})}{\bar{w}}$$from p204 $$\displaystyle \bar{w}' =p^2w_{11} + 2pqw_{12} + q^2w_{22}$$
1 | p <- 0.4 |
Problem b
1 | p <- 0.4 |
Problem c
1 | s <- 0.2 |
Problem d
$$\displaystyle \bar{w} = 1-p^2s-q^2t = 1-p^2s-(1-p)^2t$$
$$\displaystyle = 1-p^2s-(1-2p+p^2)t = 1-p^2s-t + 2tp - tp^2$$
$$\displaystyle \frac{d\bar{w}}{dp} = -2ps +2t -2tp = 0$$
Rearrange to get -2ps - 2pt =-2t or ps + pt = t or $$\displaystyle p = \frac{t}{s+t}$$ at equilbrium.
$$\displaystyle \frac{d^2\bar{w}}{dp^2} = -2s -2t < 0$$ so a maximum of $$\bar{w}$$
Box F
Problem a
Method | Formula | B=0.1 | B=0.01 | notes |
---|---|---|---|---|
Tandom | i | 1.76 | 2.66 | table p261 |
independent culling | ni’ | 3(0.88)=2.64 | 3(1.4)=4.2 | B=0.45 ,i=0.88;B=0.2 ,i=1.4 |
index selection | i$$\sqrt{n}$$ | 3.05 | 4.6 |
Problem b
$$\displaystyle I = a_1h^2_1x_1 + a_2h^2_2x_2 = (81.57)(0.47)x_1 + (20.1)(0.47)x_2$$
Box G
Problem a
$$\mu'=(p + \Delta p)^2(\mu^* + a) + 2(p + \Delta p)(q - \Delta p)(\mu^* + d) + (q - \Delta p)^2(\mu^* - a )$$Break down the equation into 3 sections and multiply out each section
Section 1:
Section 2:
Section 3:
The right most equations are:
Section 1:
Section 2:
Section 3:
Simplify and ignor terms with $$\Delta p^2$$ to give:
Section 1:
Section 2:
Section 3:
Now group by $$\mu^*$$ a and d
Combine:
Given that $\displaystyle \mu = \mu^* + a(p-q) + 2pqd$ p288
$$\displaystyle \mu' = \mu + 2 \Delta p[a + (q-p)d]$$Problem b
$$\displaystyle \mu = \mu^* + (p-q)a + 2pqd$$
So $$\displaystyle - \mu = - \mu^* + aq - ap - 2pqd$$ which is substituted into the equations. (1) $$\displaystyle \mu^* + a -u = \mu^* + a - \mu^* + aq - ap - 2pqd$$ $$\displaystyle = a(1 - p + q) - 2pqd = 2qa - 2pqd = 2q(a - pd)$$ (2) $$\displaystyle \mu^* + d -u = \mu^* + d - \mu^* + aq - ap - 2pqd$$ $$\displaystyle = d - ap + aq - 2pqd = d + a(q - p) - 2pqd = a(q - p) + d(1 - 2pq)$$ (3) $$\displaystyle \mu^* - a - u = \mu^* - a - \mu^* + aq - ap - 2pqd$$ $$\displaystyle = -a - ap + aq - 2pqd = -a(1 -q + p) - 2pqd = -a(2p) - 2pqd = -2p(a + qd)$$ (4) $$\displaystyle 2q[a + (q - p)d] - 2q^2d=2q[a+dq-dp]-2q^2d=2qa + 2qdq - 2qdp -2q^2d=2qa-2pqd=2q(a-pd)$$ (5) $$\displaystyle (q-p)[a + (q-p)d] + 2pqd=(q-p)[a+dq-dp]+2pqd=(q-p)a+(q-p)dq-(q-p)dp+2pqd=(q-p)a+dq^2-2pqd+dp^2+2pqd=(q-p)a+d(p^2+2pq+q^2-2pq)=(q-p)a + d(1-2pq)$$ (6) $$\displaystyle -2p[a + (q-p)d] - 2p^2d= -2p[a + dq - dp]- 2p^2d=-2pa - 2pdq + 2p^2d - 2p^2d= -2p(a + qd)$$Box H
carcass grade | thickness of fat | equation | |
---|---|---|---|
BMS | 7.6 | 16.8 | |
WMS | 5.9 | 10.4 | |
$$\tilde{n}$$ | 6.81 | 6.6 | |
$$V_B$$ | 0.25 | 0.97 | $$\frac{BMS-WMS}{\tilde{n}}$$ |
$$V_W$$ | 5.9 | 10.4 | WMS |
t | 0.04 | 0.085 | $$\frac{V_B}{V_B+V_W}$$ |
h^2 | 0.16 | 0.34 | 4t |
Box I
Problem a
Multiply each frequency by its phenotypic contribution to get:
$$\displaystyle 2[\bar{p}^2(1-F_{IT}) + pF_{IT}] + 2\bar{p}\bar{q}(1-F_{IT})=2\bar{p}^2(1-F_{IT}) + 2\bar{p}F_{IT} + 2\bar{p}\bar{q}(1-F_{IT})=(1-F_{IT})(2\bar{p})(\bar{p}+\bar{q}) + 2\bar{p}F_{IT}=[(1-F_{IT})+F_{IT}]2\bar{p}=2\bar{p}$$ $$\displaystyle M=2\bar{p} (above); M^2=4\bar{p}^2$$ $$\displaystyle mean square = (1-F_{IT})(4\bar{p}^2 + 2\bar{p}\bar{q}) + F_{IT}(4\bar{p})$$ $$\displaystyle Variance = V_{IT} = mean square - M^2$$ $$\displaystyle = (1-F{IT})(4\bar{p}^2 + 2\bar{p}\bar{q})+F_{IT}(4\bar{p})-4\bar{p}^2 = 2\bar{p}\bar{q}-4\bar{p}^2F_{IT}-2\bar{p}\bar{q}F_{IT}+4\bar{p}F_{IT}$$ $$\displaystyle = 2\bar{p}\bar{q}+4\bar{p}F_{IT}(1-\bar{p}-2\bar{p})\bar{q}F_{IT} = 2\bar{p}\bar{q} + 4\bar{p}\bar{q}F_{IT}-2\bar{p}\bar{q}F_{IT}$$ $$\displaystyle = 2\bar{p}\bar{q} + 2\bar{p}\bar{q}F_{IT}$$ $$\displaystyle = 2\bar{p}\bar{q}(1 + F_IT)$$Problem b
$$\displaystyle V_IS = V_IT - V_ST$$ $$\displaystyle = 2\bar{p}\bar{q}(1 + F_IT) -2F_{ST}V_0$$ $$\displaystyle = V_0(1 + F_IT) -2F_{ST}V_0$$ $$\displaystyle = V_0 + V_{0}F_IT - 2F_{ST}V_0$$ $$\displaystyle = (1 + F_IT - 2F_{ST})V_0$$Problem c
$$\displaystyle 1-F_IS = \frac{H_I}{H_S} rearrange to H_S=\frac{H_I}{1-F_IS}$$
$$\displaystyle 1-F_IT = \frac{H_I}{H_T} rearrange to H_T=\frac{H_I}{1-F_IT}$$
$$\displaystyle = 1-F_ST = \frac{H_S}{H_T} = \frac{\frac{H_I}{1-F_IS}}{\frac{H_I}{1-F_IT}}= \frac{H_I}{1-F_IS}\frac{1-F_IT}{H_I}=\frac{1-F_IT}{1-F_IS}$$
$$\displaystyle or (1-F_IS)(1-F_ST)= 1-F_IT$$
A second method would be start with $$\displaystyle (1-F_IS)(1-F_ST)= 1-F_IT$$
and substitute in to show equality:
$$\displaystyle (1 - \frac{H_S - H_I}{H_S})(1-\frac{H_T-H_S}{H_T})= 1 - \frac{H_T - H_I}{H_T}$$
$$\displaystyle (\frac{H_S}{H_S} - \frac{H_S - H_I}{H_S})( \frac{H_T}{H_T}-\frac{H_T-H_S}{H_T})= \frac{H_T}{H_T} - \frac{H_T - H_I}{H_T}$$
$$\displaystyle ( \frac{H_S - (H_S - H_I)}{H_S})(\frac{H_T - (H_T-H_S)}{H_T})= \frac{H_T - (H_T - H_I)}{H_T}$$
$$\displaystyle (\frac{H_I}{H_S})(\frac{H_S}{H_T})=\frac{H_I}{H_T}$$
$$\displaystyle \frac{H_I}{H_T} = \frac{H_I}{H_T}$$
Problem d
1 | N <- 20 |
Box J
Problem a
1 | t <- 0.15 |
Box K
Problem a
1 | r <- 0.28 |
Problem b
$$\displaystyle h^2 = \hat{h}^2(\frac{1-A}{1-\hat{h}^2}A)$$ substitute $$\hat{h}^2=\frac{A}{r}$$ $$\displaystyle h^2 = \frac{A}{r}(\frac{1-A}{1-\frac{A}{r}}A)$$ = $$\frac{A-A^2}{r-A^2}$$ rearrange to get $\displaystyle h^2(r-A^2)=A-A^2$ $$\displaystyle h^2(r-A^2)-A+A^2=0$$ $$\displaystyle h^2r-h^2 A^2-A+A^2=0$$ $$\displaystyle h^2-A+A^2(1-h^2)=0$$Problem c
1 | sig2.p <- 60 |
Box L
Problem a
1 | B <- 0.01 # freq in parents |
Problem b
1 | F.p <- 0.001 |
From Box C p261 the corresponding probablity that a child is affected is 0.05.